IMPLEMENTASI 4 PILAR PENATALAKSANAAN DIABETES MELLITUS MENINGKATKAN KEPATUHAN MINUM OBAT PENDERITA DIABETES MELLITUS - Pauzan Efendi; Erni Buston; Septiyanti Septiyanti (Poltekkes Kemenkes Kalimantan Timur, 2021)
Diabetes Mellitus (DM) is a chronic disease that occurs due to the pancreas not producing enough insulin. Complications of diabetes mellitus must be prevented as early as possible. Management of diabetes mellitus can be obtained effectively if individuals have the knowledge to carry out DM management behaviors. The purpose of this study was to determine the effect of the implementation of the 4 Pillars of diabetes mellitus management on medication adherence to diabetes mellitus patients at Puskesmas Kandang Kota Bengkulu 2020. The research design was quasi-experimental with pre-test and post-test with control group design. The number of samples was 50 people consisting of 25 people in the intervention group and 25 people in the control group. The sampling technique is purposive sampling. Measuring medication adherence using the SEDM instrument which consists of 40 items. Analysis using t-test at α <5%. The results of this study the mean pre-intervention group knowledge was 4,56 with a standard deviation of 1,003 and the mean post knowledge was 6,88 standard deviation 1,013, while the mean pre-control group knowledge was 3,20 with a standard deviation of 0,707. The mean post knowledge was 3,72 standard deviation 0,678. There is an effect of implementing the 4 pillars of diabetes mellitus management on adherence to taking medication for diabetes mellitus sufferers. The implementation of the 4 pillars of diabetes mellitus management can improve compliance with taking medication in diabetes mellitus patients at Puskesmas Kandang, Bengkulu City. It is hoped that patients and families who have been exposed to the implementation of the 4 pillars of DM management are able to apply this therapy independently.